Tombouctou, 1591. À la croisée des migrations en Afrique - Rémi Dewière (Diasporas: Circulations, Migrations, Histoire)
In 1591, a Moroccan army was sent by Sultan Aḥmad al-Manṣūr to conquer the city of Timbuktu. This army was composed of renegades, Andalusian refugees, and Moroccan soldiers from the Dra’a and Fez. These men and their descendants established a new order in the city, modifying its social structure and its architecture. Timbuktu was then at the crossroads of migrations: a terminus for some, a point of departure for others fleeing the Moroccan invasion. The capture of Timbuktu was the result of and the starting point for profound changes in Africa in the modern era.